2015
DOI: 10.3109/10715762.2015.1085978
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione S-transferase P1 suppresses iNOS protein stability in RAW264.7 macrophage-like cells after LPS stimulation

Abstract: Glutathione S-transferase P1 (GSTP1) is a ubiquitous expressed protein which plays an important role in the detoxification and xenobiotics metabolism. Previous studies showed that GSTP1 was upregulated by the LPS stimulation in RAW264.7 macrophage-like cells and GSTP1 overexpression downregulated lipopolysaccharide (LPS) induced inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) expression. Here we show that GSTP1 physically associates with the oxygenase domain of iNOS by the G-site domain and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 33 publications
4
28
0
Order By: Relevance
“…Subsequent studies examining activated macrophages demonstrated that silencing Mrp1 resulted in an intracellular accumulation of DNICs, while silencing Gstp1 in these cells augmented the release of iron-59 out of the cell (as DNICs) [ 8 ]. Another intriguing GSTP1-NO interaction has been suggested by studies demonstrating the binding of GSTP1 to iNOS [ 5 ]. In this later study, GSTP1 was shown to directly interact with the oxygenase domain of iNOS through the GSTP1 G-site domain [ 5 ].…”
Section: Gsts and Emerging Roles In No Metabolismmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequent studies examining activated macrophages demonstrated that silencing Mrp1 resulted in an intracellular accumulation of DNICs, while silencing Gstp1 in these cells augmented the release of iron-59 out of the cell (as DNICs) [ 8 ]. Another intriguing GSTP1-NO interaction has been suggested by studies demonstrating the binding of GSTP1 to iNOS [ 5 ]. In this later study, GSTP1 was shown to directly interact with the oxygenase domain of iNOS through the GSTP1 G-site domain [ 5 ].…”
Section: Gsts and Emerging Roles In No Metabolismmentioning
confidence: 99%
“…While GSTs are traditionally associated with detoxification mechanisms due to their ability to conjugate glutathione (GSH) to toxins for excretion, recent advances have explored the role of GSTs in NO metabolism [ 5 , 6 , 7 , 8 , 9 , 10 ]. Studies investigating the extensive role of NO in vascular reactivity have identified GSTs as targets for the biotransformation of organic nitrates, including nitroglycerin, that results in vasodilation [ 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…21,22 Later, further studies proved RAW264.7 cells could respond to stimuli in vitro and subsequently generate multinucleated cells with the hallmark characteristics expected for fully differentiated osteoclasts (RAW-OCs). RAW264.7 cell linage is well-characterized with regard to macrophage-mediated immune, metabolic and phagocytic functions 21 and is increasingly used and accepted as a cellular model of osteoclastogenic study; [24][25][26] however, with the vastly usage of RAW-OCs for understanding the osteocalstogenesis in the past two decades, there raised considerable requirements for the extensively understanding the RAW-OCs and associated cellular biological mechanisms. RAW264.7 cell linage is well-characterized with regard to macrophage-mediated immune, metabolic and phagocytic functions 21 and is increasingly used and accepted as a cellular model of osteoclastogenic study; [24][25][26] however, with the vastly usage of RAW-OCs for understanding the osteocalstogenesis in the past two decades, there raised considerable requirements for the extensively understanding the RAW-OCs and associated cellular biological mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…23 Therefore, RAW-OCs can be used for studying osteoclastogenesis through different methods for various study purposes, including: biochemical, immunological, physiological, molecular and functional assays according to various study procedures. RAW264.7 cell linage is well-characterized with regard to macrophage-mediated immune, metabolic and phagocytic functions 21 and is increasingly used and accepted as a cellular model of osteoclastogenic study; [24][25][26] however, with the vastly usage of RAW-OCs for understanding the osteocalstogenesis in the past two decades, there raised considerable requirements for the extensively understanding the RAW-OCs and associated cellular biological mechanisms. 27,28 On the other hand, document studies reported that during the osteoclastic induction, various stimuli might lead different cellular fates during the RAW-OC induction.…”
Section: Introductionmentioning
confidence: 99%